Emergency Preparedness and Response (EP&R) : Case Study of Japan - World Bank (Washington, DC, 2022)
This case study extracts translatable and transferable lessons learned from the evolution of disaster risk management (DRM) in Japan by focusing on the country’s emergency preparedness and response (EP&R) system. Chapter 1 describes the present state of the DRM system in Japan from a holistic viewpoint, with case studies of three major disasters that have influenced the process by which legal and institutional frameworks for the country’s disaster management have been amended: the Isewan Typhoon in 1959, the Great Hanshin-Awaji Earthquake (Kobe Earthquake) in 1995, and the Great East Japan Earthquake and Tsunami (GEJET) in 2011. Chapter 2 describes facilities, equipment, and information systems for DRM, while chapter 3 elaborates on personnel management, citizen engagement, and cooperation mechanisms in Japan. Chapter 4 highlights four lessons learned from Japan’s disaster preparedness and response experiences relevant for developing countries that could face similar disasters.